De cisco a bioestimulantes: maricultura de macroalgas marinha como fonte de renda e de desenvolvimento sustentável em Rio do Fogo-RN - Silva Neto, Heronildes Lima da (Universidade Federal Rural do Semi-Árido, 2020)
Mariculture is the cultivation of marine organisms in their natural habitats, usually for commercial purposes. The marine macro-algae mariculture carried out in Rio of Fogo - RN is developed along the lines of family aquaculture. The objective of this work is to identify the sustainability of this activity by the farmers. Initially, a bibliographic review was carried out, mainly articles and journals by authors that address this topic. In a second moment, field research was carried out in the community of Rio of Fogo-RN, with the farmers of that locality. The results demonstrate that the development of this practice, gives value to the communities, promotes the occupation of labor and generates income for the families. In addition, it is an activity that does not depend on external agents, since the farmers themselves operate throughout the entire production chain, from the cultivation of macroalgae, through processing and ending with the marketing of the final product. Macroalgae mariculture has provided diverse knowledge, enriching the educational field, as it reveals traces of the economy and culture of the coast of Rio Grande do Norte.
Keywords: Aquicultura; Algas; Rio do Fogo; Cultura; Aquaculture; Seaweed; Rio of Fogo; Culture; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL